The political dimension in the speech of the director, author (Dawoud Abdel Sayed) Citizen film, informant and thief (amodel): احمد جبار عبد الكاظم (Al-Academy, 2020)
The research addresses the questioning of political loads in a cinematic model from the films of the author (David Abdel Sayed), who has been busy throughout his films in criticizing political power, where he presented protests visions her body the artistic composition of cinematic means of expression through artistic treatments that facilitate the representations of modernity in contemporary cinematic trends, and by this Several contemporary cinematic criticism is an example of a thinker cinematographer who presents his critical thesis on power politics through the composition of the film (material - form - expression). The research consisted of four chapters. The first was a methodological framework that included the research problem of the question: What is the manner or artistic formulation of the film's means of expression, through which the author (David Abdel Sayed) managed to embody the political issue, the importance of research and the need for it, and the limits of the research that were limited to a cinematic model, which is the movie "Citizen, Informer, and Thief" and the second chapter. The theoretical, which included two subjects, the first is related to the concern of cinematic art with politics, and the second is formal, which includes the possibilities of directorial processing in expressing political loads. As for the third chapter, which is the research procedures and sample analysis according to the theoretical framework indicator attached to the results and conclusions